Do children use logic to spell logician? Implicit versus explicit teaching of morphological spelling rules - Burton, L; Nunes, T; Evangelou, M (Wiley, 2021)
BACKGROUND: Intervention studies have reported the advantage of teaching children about morphemes for spelling, but direct comparisons between explicit and implicit teaching have been examined systematically in relation to only a few morphological rules. AIMS: This study compared explicit versus implicit teaching of the functional rule for the conservation of stem morphemes in derived words in English (e.g., logic is conserved in the derivative logician in spite of changes in pronunciation). SAMPLE: Participants (n = 90; 7- to 9-year-olds) were drawn from three schools with a diverse intake. METHODS: The design included a pre-test and two post-intervention tests. Participants were randomly assigned to one of three groups: an explicit group, taught about stems and their conservation in derived words; an implicit group, exposed to the same stems and derivatives without explicit teaching; and an unseen control group. At pre- and post-test, the children's spelling of stems in derivatives was assessed. The interventions involved practice games in which the children spelled derived words after seeing the base forms; the explicit group discussed the connection between the spellings, whereas the implicit group did not. RESULTS: Analyses of variance revealed that explicit teaching led to more significant spelling improvements than implicit or no teaching, and this effect held at both post-tests. CONCLUSIONS: It was concluded that explicit teaching of the stem conservation rule in derived forms combined with appropriate practice games shows a sustained effect on spelling. The evidence supports explicit teaching of this morphological rule in classroom practice.